MASMe: Developing Mobile Accounting Software for Micro Entrepreneurs - Mohd Nasir, Mohd Herry; Abdul Talib, Yurita Yakimin (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
In this study, a new mobile accounting application called MASMe has been developed to assist microentrepreneurs in the area of financial management and accounting. The MASMe prototype helps to simplify finance and accounting processes and produce real-time reporting both online and offline. This will help micro-entrepreneurs to understand the accounting concepts and to obtain information to help manage their business and better decision-making. The system will also enable micro-entrepreneurs to apply for business loans and government grants from government agencies and banks to expand their business. As mobile accounting software, MASMe is reasonably simple and straightforward and uses the simple concept of money-in and money-out (i.e. cash flow) given many micro-entrepreneurs have limited finance and accounting knowledge. Employing the Waterfall method of the System Development Life Cycle (SLDC) the requirements of users were collected, and the design of the model was constructed using the Unified Modelling Language (UML) technique. The model was validated and tested through the development of the prototype with feedback received from users of the system. While several inherent limitations were noted, these limitations are expected to be overcome in future versions of the application with the ability to print invoices, export data into Microsoft Excel and to expand the loan payment function of the application to benefit microentrepreneurs.